1998
DOI: 10.1038/sj.onc.1201802
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitogen activated protein (MAP) kinase cascade potentiates cell killing by low dose ionizing radiation in A431 human squamous carcinoma cells

Abstract: The molecular mechanism(s) by which tumor cells survive after exposure to ionizing radiation are not fully understood. Exposure of A431 cells to low doses of radiation (1 Gy) caused prolonged activations of the mitogen activated protein (MAP) kinase and stress activated protein (SAP) kinase pathways, and induced p21 Cip-1/WAF1 via a MAP kinase dependent mechanism. In contrast, higher doses of radiation (6 Gy) caused a much weaker activation of the MAP kinase cascade, but a similar degree of SAP kinase cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
99
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 39 publications
(94 reference statements)
11
99
0
Order By: Relevance
“…We have proposed a scheme to illustrate the manner in which FGF2 predominantly activates ERK2 and stimulates sustained FGF1 and Bcl-x production (Figure 8). The importance of the long-term activation of ERK2 for cell survival is consistent with studies showing that acute activation of the ERK cascade by growth factors potentiates proliferation whereas a chronic increase in ERK activity is cytoprotective (Carter et al, 1998). In addition, it was shown that overproduction of ERKs in human breast cancer was required for cell survival (Sivaraman et al, 1997) and that cell survival is correlated with the overproduction of ERK2 during aging of RPE cells (Guillonneau et al, 1998b).…”
Section: Discussionsupporting
confidence: 78%
“…We have proposed a scheme to illustrate the manner in which FGF2 predominantly activates ERK2 and stimulates sustained FGF1 and Bcl-x production (Figure 8). The importance of the long-term activation of ERK2 for cell survival is consistent with studies showing that acute activation of the ERK cascade by growth factors potentiates proliferation whereas a chronic increase in ERK activity is cytoprotective (Carter et al, 1998). In addition, it was shown that overproduction of ERKs in human breast cancer was required for cell survival (Sivaraman et al, 1997) and that cell survival is correlated with the overproduction of ERK2 during aging of RPE cells (Guillonneau et al, 1998b).…”
Section: Discussionsupporting
confidence: 78%
“…However, the mechanisms by which radiation can either increase cell death or alter the proliferative rate of surviving cells are not understood. Recently, radiation has been shown to activate multiple signaling pathways within cells which can alter cell survival or proliferation depending upon the radiation dose, the cell type, and the culture conditions (Carter et al, 1998;Xia et al, 1995;Chmura et al, 1997;Santana et al, 1996). Several groups have shown that the epidermal growth factor receptor (EGFR, also called ErbB1) is activated in response to irradiation of squamous and mammary carcinoma cells (Carter et al, 1998;Schmidt-Ullrich et al, 1997;Kavanagh et al, 1998;Balaban et al, 1996;Dent et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms by which ionising radiation has been shown to induce apoptosis is via activation of the stress-activated protein kinase pathway, also known as the c-Jun N-terminal kinase (SAPK/JNK) pathway (Verheij et al, 1996). However, ionising radiation can also result in the activation of EGFR which, via activation of the ras/raf mitogen-activated protein kinase (MAPK) cascade, exerts a delicate inhibitory effect upon the SAPK/JNK pathway and therefore can afford a degree of protection from the proapoptotic effects of ionising radiation (Carter et al, 1998;Verheij et al, 1998). Inhibition or an imbalance of downstream signalling cascades via an EGFR-TKI may disrupt this inbuilt protective mechanism and increase radiation-induced cell death.…”
Section: Discussionmentioning
confidence: 99%